2006
DOI: 10.1002/jbm.b.30557
|View full text |Cite
|
Sign up to set email alerts
|

Porous hybrid structures based on P(DLLA‐co‐TMC) and collagen for tissue engineering of small‐diameter blood vessels

Abstract: Poly (D,L-lactide)-7co-(1,3-trimethylene carbonate) [P(DLLA-co-TMC)] (83 mol % DLLA) was used to produce matrices suitable for tissue engineering of small-diameter blood vessels. The copolymer was processed into tubular structures with a porosity of approximately 98% by melt spinning and fiber winding, thus obviating the need of organic solvents that may compromise subsequent cell culture. Unexpectedly, incubation in culture medium at 37 degrees C resulted in disconnection of the contact points between the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
(60 reference statements)
0
16
1
Order By: Relevance
“…Several studies have reported the fabrication of poly(DLLA‐ co ‐TMC) (abbreviated as PLMC) and the optimization of their thermal, physical, mechanical, and biodegradable properties by modulating the ratios of the monomers . In previous research, this copolymer with approximately 80 mol % of DLLA behaved well as biomaterial with high attachment and proliferation with human cells, displaying adequate material–cell interactions . However, the application of this biodegradable copolymer is far from fully exploited, as its intrinsic shape‐changing characteristics are rarely focused .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the fabrication of poly(DLLA‐ co ‐TMC) (abbreviated as PLMC) and the optimization of their thermal, physical, mechanical, and biodegradable properties by modulating the ratios of the monomers . In previous research, this copolymer with approximately 80 mol % of DLLA behaved well as biomaterial with high attachment and proliferation with human cells, displaying adequate material–cell interactions . However, the application of this biodegradable copolymer is far from fully exploited, as its intrinsic shape‐changing characteristics are rarely focused .…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, such fibers can be produced by electrospinning, a powerful technique used to produce an array of biomaterials that mimic the pores, ridges, fibers, and other features in the natural extracellular matrix. [11][12][13][14][15][16] For example, electrospun segmented polyurethane is widely used in a variety of medical devices and experimental tissue engineering scaffolds to take advantage of an optimal combination of chemical and mechanical properties. [17][18][19][20] Indeed, segmented polyurethane also has potential as small-diameter blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they show poor mechanical properties compared to synthetic degradable polymers and are most commonly used as coatings on biostable grafts. Several synthetic degradable polymers have been proposed, mainly aliphatic biodegradable polyesters like poly(lactic‐ co ‐glycolic acid) (PLGA),32, 33 poly(lactic acid) (PLA),34–37 but also polycarbonate derivatives38, 39 or polydioxanone,40 since they are already in use in some biomaterial and drug delivery applications. The main problem encountered with these synthetic biodegradable polymers is their rapid loss of mechanical properties, which is due to an accelerated in vivo biodegradation of the nanofibers as a direct consequence of their very high surface/ volume ratio.…”
Section: Introductionmentioning
confidence: 99%